2018
DOI: 10.1016/j.socscimed.2018.04.050
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intimate partner violence on women's contraceptive use: Evidence from the Rakai Community Cohort Study in Rakai, Uganda

Abstract: A systematic review of longitudinal studies suggests that intimate partner violence (IPV) is associated with reduced contraceptive use, but most included studies were limited to two time points. We used seven waves of data from the Rakai Community Cohort Study in Rakai, Uganda to estimate the effect of prior year IPV at one visit on women's current contraceptive use at the following visit. We used inverse probability of treatment-weighted marginal structural models (MSMs) to estimate the relative risk of curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…These can be explained by the fact that the partners of males who experience IPV will most likely practice contraception to avoid unwanted pregnancies and thus empower themselves since sexual IPV was the most common form of IPV perpetrated by the males in this current study. Contrary to our research, Maxwell et al 2018, discovered that in Uganda, perpetration of IPV resulted in reduced odds of using methods of contraception that require the cooperation of both partners like condoms. This due to the inability of the spouses of the males to negotiate the use of such methods (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…These can be explained by the fact that the partners of males who experience IPV will most likely practice contraception to avoid unwanted pregnancies and thus empower themselves since sexual IPV was the most common form of IPV perpetrated by the males in this current study. Contrary to our research, Maxwell et al 2018, discovered that in Uganda, perpetration of IPV resulted in reduced odds of using methods of contraception that require the cooperation of both partners like condoms. This due to the inability of the spouses of the males to negotiate the use of such methods (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…While some women may prefer other options, their range is limited to those methods that have clandestine use abilities. Previous research has shown that women in relationships where intimate partner violence prevails are unlikely to use and continue use of their preferred methods [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…2014), Sexual Relationship Power Scale (Pulerwitz, Gortmaker, and DeJong 2000), and the influence of IPV on contraceptive use (Macquarrie, Mallick, and Kishor 2016; Maxwell et al. 2018). Further, qualitative research highlights the occurrence of pregnancy pressures in high fertility LMIC settings (Grace and Fleming 2016).…”
Section: Introductionmentioning
confidence: 99%